Efektivitas Metode Sorogan Dalam Meningkatkan Keterampilan Membaca Kitab Kuning Di Pondok Pesantren Al-Chikmatul Muballigoh Serang–Banten - Khofiya, Nida; Andy Hadiyanto; Muhamad Rudi Barnansyah (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
This research aims to analyze and describe the effectiveness of the sorogan method in improving yellow book reading skills, as well as analyzing the sorogan method in improving mechanical skills and understanding meaning at the Al-Chikmatul Muballigoh Islamic Boarding School. The approach in this research is a qualitative approach with the method used is qualitative descriptive analysis. The data in this research are the sources in the form of observations, interviews, and information contained in various activities at the Al-Chikmatul Muballigoh Islamic Boarding School which is located at Kp. Sindanghuela District. Pabuaran District. Serang – Banten. The theories used in this research are the theory of learning effectiveness, the sorogan method, and reading ability. The results of this research indicate that learning uses the walking method effectively. It is said to be effective because the students showed a good increase in understanding, speed and accuracy in reading the yellow book after applying the sorogan method as the results of interviews conducted by researchers showed that there was an increase in grade promotion this year after using the sorogan method compared to the previous year. Thus, the slogan method has proven to be effective in improving yellow book reading skills because it shows that learning activities are carried out in a scheduled and structured manner, and students also get the opportunity to discuss directly with their ustadz/ustadzah.